HIKES (WALKS) IN THE NATURE AS LEISURE: FROM THE EXPERIENCES OF INVOLVEMENT TO THE SPIRITUALITY (Fiep Bulletin - online, 2013)
Values such as reason, knowledge and science were important criteria for evaluating the mentality of the progress of human societies until the last century. From the nineteenth century on, the idea of progress, evident in the West, in a sense of development of material, moral and spiritual aspects, seems that is being redefined taking into account the new approaches related to modernity, to the valuation of the individual, to the construction of the self, to the spirituality, to the morality and to the religion. Considering the current context of valuation of the environment, of re-enchantment of activities related to the practices in nature, and the multiple senses given to such practices, it emerges the goal that gives source to this study: to analyze the presence of the idea of spirituality in activities considered as of leisure, held in touch with nature. This is a descriptive, exploratory and qualitative research. The data were collected from two theses held in the Post Graduate Program of the UGF (PPGUGF), in Rio de Janeiro, tied to the line of investigation Leisure, Culture and Adventure Sports (PASSOS, 2004; CARDOSO, 2006). The theoretical reference was based on Almeida (2008), Heintzman (2000, 2003), Deschenes (2002), among other authors. The connections among leisure, spirituality and sensitivities entered through body makes it possible to think of a recreational and bodily spirituality expressed by pilgrim walkers related to the most traditional movements such as that of the Caminho de Santiago de Compostela or to the trekking chosen as a form of leisure. The interconnection among the components of leisure: time, activity in nature and attitude; and the spirituality offer conditions to raise the harmony in the lives of these walkers.
Keywords: walk (hike); leisure in nature; leisure and spirituality